Konsep Menuntut Ilmu dalam Perspektif Al-Qur’an dan Hadis serta Relevansinya pada Era Modern - Bagas; Berliana Azizah; Rizqa Zakiyah; Alihan Satra (Yayasan Al-Afif, 2026)
This study examines the concept of seeking knowledge in the perspective of the Qur'an and Hadith and its relevance in the modern era. The problem addressed is the declining understanding of the spiritual and moral dimensions of knowledge, as many people view education merely as a means of achieving material success. This study aims to analyze the principles of seeking knowledge in Islam and their application in daily life. The research employed a qualitative descriptive approach using library research. Data were collected through documentation of primary sources, namely the Qur'an and Hadith, and supported by relevant literature on Islamic education. The findings indicate that seeking knowledge is an obligation for every Muslim and serves both spiritual and social purposes. Knowledge elevates human dignity, strengthens faith, and contributes to societal welfare. The study concludes that the values of sincerity, perseverance, lifelong learning, and respect for teachers remain highly relevant for developing Islamic education and character in contemporary society.